1998
DOI: 10.1039/a807835a
|View full text |Cite
|
Sign up to set email alerts
|

A new redox-tunable near-IR dye based on a trinuclear ruthenium(II) complex of hexahydroxytriphenylene

Abstract: The complex [{Ru(bipy) 2 } 3 (m 3 -L)] 3+ (H 6 L = hexahydroxytriphenylene), in which the tris-dioxolene bridging ligand is formally in the tris-semiquinone oxidation state [sq,sq,sq], undergoes three reversible ligand-centred oxidations to the [q,q,q] state (q = quinone); it exhibits very strong NIR absorption arising from Ru ? L charge transfer whose maximum wavelength may be tuned over a wide range according to oxidation state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 8 publications
2
42
0
2
Order By: Relevance
“…Phthalocyanine is chosen as the planar bridging unit because of its redox activity and good carrier transport ability based on the large delocalized π system . The catechol derivatives are known to form square‐planar complexes with metal ions which show redox activity, based on the reversible interconversions between catechol, semiquinone, and quinone forms . The crystalline and porous structure of Cu‐CuPc was characterized by powder X‐ray diffraction (PXRD) and gas adsorption measurements.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Phthalocyanine is chosen as the planar bridging unit because of its redox activity and good carrier transport ability based on the large delocalized π system . The catechol derivatives are known to form square‐planar complexes with metal ions which show redox activity, based on the reversible interconversions between catechol, semiquinone, and quinone forms . The crystalline and porous structure of Cu‐CuPc was characterized by powder X‐ray diffraction (PXRD) and gas adsorption measurements.…”
Section: Figurementioning
confidence: 99%
“…The broad peaks would be the mixture of the redox peaks of copper phthalocyanine and catecholate units. It has been reported that the ring‐based redox of phthalocyanine and the interconversion between catechol, semiquinone, and quinone show multiple redox peaks within the potential range from 2.0 to 4.4 V versus Li/Li + . Copper(II) ions are known to be electrochemically inactive in the examined range …”
Section: Figurementioning
confidence: 99%
“…Yellowlees e colaboradores 72 Similarmente, o complexo dinuclear [2] n+ (n=0-4), em que o ligante é uma unidade de tri-hidroxifluorona com dois sítios de dioxoleno queladosa figura 19 mostra a estrutura deste complexo para n = +1 -, apresenta três processos de oxirredução reversíveis e a oxidação dos ligantes resultam em buracos (holes) de baixa energia no siste a π, esulta do, ai da, e t a sições do tipo transferência de carga metal-ligante (MLCT) nas espécies oxidadas. 73 74 possuindo quatro estados redox estáveis baseados na interconverção redox do ligante, a partir de sq-sq-sq para q-q-q, de acordo com a figura 20, onde sq = unidade semiquinona e q = unidade quinona. A transferência de carga metal ligante, (MLCT do Ru(II) para o ligante, movimenta as bandas de absorção no espectro UV-Vis-NIR de 1170 nm (sq-sq-sq) para 759 nm (q-q-q), com intensidades maiores que 70000 dm 3 mol -1 cm -1 , com as etapas de oxidação do ligante.…”
Section: Figura 18unclassified
“…(Schweigert et al 2001) The conjugated electron structure of the planar HHTP also confers interesting electrochemical and spectroscopic properties, which have been little investigated. Ward and co-workers (Barthram et al 1998;Barthram et al 2000;Grange et al 2010) investigated inorganic complexes of HHTP with ruthenium and osmium, and their electrochemical and spectroscopic properties. The trinuclear ruthenium complex is stable in the trissemiquinone oxidation state, and can exhibit up to six redox processes.…”
Section: R a F T D Introductionmentioning
confidence: 99%